Analisis User Interface User Experience Situs Website Media Indonesia Menggunakan Metode Design Thinking - Muhammad Dwi Ikhwannudin; Ridha Sefina Samosir (UNIVERSITAS KALBIS, 2026)
Media Indonesia is a digital media that was founded on January 19, 1970, starting from print media and developing into digital news. Media Indonesia has an unfavorable assessment on the average access duration of visitors website only 1 minute 16 seconds and a bounce rate with a value of 70.29% which is quite large. With this condition, the researcher proposes to analyze the user interface user experience of Media Indonesia to identify features that are good and still need to be improved or added. This research uses the design thinking method, Figma to design a new interface and a user experience questionnaire for testing. The results of user interface testing showed excellent results on the scale of attractiveness, clarity, and novelty, and good results on the scale of efficiency, accuracy, and stimulation. With this information, the researcher reorganized the user interface and user experience design accordingly.